Keeping kids safe, healthy, and smart [ - Williams, Kimberly; Lebrun, Marcel , 1957- (Lanham, Md : Rowman & Littlefield Education, 2009)
For all adults who interact with kids, whether they be parents, teachers, or other caregivers. Provides specific suggestions for keeping children safe from hidden and open dangers wherever they spend time. Major threats and hidden dangers to children in our country are examined, including threats in school; threats in cyberspace (bullying or harassment and child predators or child pornography), and a wide range of other threats such as self-mutilation, accidents, abuse, drugs, and mental illness
Description based on print version record
Includes bibliographical references
Keywords: Children's accident -- United States -- Prevention